2021
DOI: 10.1371/journal.pone.0246493
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different Zinc (Zn) levels on growth and nutrient uptake of Basil (Ocimum basilicum L.) grown under salinity stress

Abstract: Salinity is among the most important abiotic stresses, which negatively affect growth, nutrient uptake and yield of crop plants. Application of different micronutrients, particularly zinc (Zn) have the potential to ameliorate the negative impacts of salinity stress. However, the role of Zn in improving salinity tolerance of basil (Ocimum basilicum L.) is poorly understood. This study evaluated the impact of different Zn levels (0, 5 and 10 mg kg-1) on growth and nutrient acquisition traits of basil under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 47 publications
4
36
0
2
Order By: Relevance
“…Similarly, S is an integral part of several important compounds in plants, such as vitamins, coenzymes, and phytohormones (Li et al, 2020). In addition, Zn 21 reduces excessive Na 1 uptake under saline conditions by affecting the structural integrity and permeability of cell membrane (Tolay, 2021). However, Yildiz et al (2020) reported that Na 1 and Cl À ions compete with nutrients and lead to nutrient deficiency in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, S is an integral part of several important compounds in plants, such as vitamins, coenzymes, and phytohormones (Li et al, 2020). In addition, Zn 21 reduces excessive Na 1 uptake under saline conditions by affecting the structural integrity and permeability of cell membrane (Tolay, 2021). However, Yildiz et al (2020) reported that Na 1 and Cl À ions compete with nutrients and lead to nutrient deficiency in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Basil ( Ocimum basilicum L.) is an important warm-season MAP with high potential to be integrated into a wealth of cropping systems [ 14 , 15 ]. The salinity tolerance of basil is considered low [ 16 ], and the variability of the responses depends on numerous factors that include the genotype, the growing medium and conditions, including the presence in the soil of microbes with either pathogenic or beneficial activity [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Such responses are multidimensional because they affect main parameters of economic importance, such as the leaf fraction on the total above-ground biomass, and the concentration and composition of secondary compounds, including the volatile organic fractions and the essential oil [ 14 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In PC1, the positive correlation within S and Zn is well recognized since Zn−S bonds serve as structural braces in protein domains that participate in several molecule interactions [ 28 ]. In the same context, Zn application improved K uptake, under normal as well as saline conditions, by basil ( Ocimum basilicum L.) [ 29 ], while K was the unique element amongst those measured, which showed a positive correlation with S content in shoots of the Chinese cabbage, highlighting its role as a counter cation for sulfate during xylem loading and vacuolar storage in leaves [ 30 ]. In PC2, the positive correlations between Ca and Sr are explained by their similar chemical and physical properties as a result of the similarity of the outer electron structure of these elements [ 27 ].…”
Section: Discussionmentioning
confidence: 99%